Another Path to Belonging: A Case Study of Middle School Students' Perspectives. (13th June 2016) - Green, Marissa; Emery, Alyssa; Sanders, Megan; Anderman, Lynley H.
Abstract : This qualitative study explored students' experiences in a small, early-college secondary school in the United States that intentionally aims to create a culture promoting accelerated academic achievement, particularly in the areas of science, technology, engineering, and math (STEM). Past research in the fields of both educational and developmental psychology has suggested that students' sense of belonging plays a significant role in their social and academic functioning. Few studies, however, have explored how students' sense of belonging is supported in settings that emphasise accelerated academic performance. The present study focused on students' own understanding of the factors that contribute to their sense of belonging in this academically rigorous environment and extends current accounts of belonging, most of which have been quantitative in nature. The results of the present study highlight a distinction between social and academic belonging. Social belonging originated from students' descriptions of their relationships with teachers and friends, alongside a noted lack of bullying behaviour, and an open and accepting social environment. Academic belonging originated from students' accounts of meeting rigorous expectations, participating in a range of educational opportunities, receiving academic support from teachers, and sharing similar academic interests with peers. Some students reported experiencing one type of belonging without the other, suggesting that social and academic belonging are distinct aspects of students' overall sense of school belonging. Future research should examine whether academic belonging provides an alternative pathway to the sense of school belonging in academic environments beyond the context examined in the present study.